Skin Tightening With Hyperdilute CaHA: Dilution Practices and Practical Guidance for Clinical Practice. (30th June 2021) - Lorenc, Z Paul; Black, Jeanette M; Cheung, Jessie S; Chiu, Annie; Del Campo, Roberta; Durkin, Alan James; Graivier, Miles; Green, Jeremy B; Kwok, Gideon P; Marcus, Keith; Rammos, Charalambos "Babis"; Werschler, William Philip
Abstract: Background: Over the past several years, hyperdilute calcium hydroxylapatite (CaHA) has emerged as an effective modality for improving skin quality and managing laxity in the face, arms, hands, neck, décolletage, upper arms, abdomen, buttocks, and upper legs, as well as for treating cellulite and striae. Whereas undiluted CaHA is used to provide volume, hyperdilute CaHA is distributed across a much larger surface area in a more superficial plane to stimulate neocollagenesis and elastin formation over time. The absence of lymphocytic infiltrates and predominance of type 1 collagen in the tissue response to CaHA make hyperdilute CaHA a valuable tool for nonsurgical skin tightening. Objectives: The aim of this study was to provide practical step-by-step guidance on patient selection, dilution practices, and optimal injection technique to facilitate incorporation of the technique into clinical practice. Methods: Over the course of 3 regional meetings in the United States, 12 expert physician injectors participated in live webinars as part of a continuing medical education program. Results: The practical guidance in this manuscript is based upon the most frequently requested information by audience members and the information considered critical for success by the authors. Conclusions: The minimally invasive nature of filler injection results in little downtime, making this treatment particularly appealing. The recommendations presented are consistent with previously published consensus guidelines on hyperdilute CaHA but are intended to serve as "how-to" guidance based on the experience of expert injectors who have successfully treated the face and body. Level of Evidence: 4: